(untitled) (Research, Society and Development, 2021)
Objective: To find out how nursing care is developed for children and adolescents with special health needs hospitalized in a pediatric inpatient unit. Methodology: Qualitative, descriptive and exploratory research carried out in a pediatric inpatient unit with nine nursing professionals. Data collection took place through semi-structured interviews with audio-recorded statements and after the double transcription, the statements were subjected to thematic content analysis. Results: Nursing professionals develop care based on scientific knowledge and through play. The professionals have the support of the family, and use empathy, communication and bonding as promoting sources for this care. Final Considerations: Nursing care is based on scientific evidence and focused on family involvement as co-participant. These principles are essential for nursing care and assistance to children and adolescents with special hospitalized needs.